Impact of deceased organ donor injection drug use on donor culture positivity and recipient outcomes. Issue 6 (30th August 2022) - Moore, Krista; Lautenbach, Ebbing; Blumberg, Emily A.; Han, Jennifer; Lee, Dong Heun; Clauss, Heather; Hasz, Richard; Bilker, Warren B.; Molnar, Esther; Alimenti, Darcy; West, Sharon; Tolomeo, Pam; et al.
Abstract: Background: Due to the ongoing opioid epidemic in the United States, deceased organ donors increasingly have a history of injection drug use (IDU), raising concerns about infectious risks to solid organ transplant (SOT) recipients. We sought to determine how recent IDU among deceased organ donors impacted donor culture results and recipient outcomes. Methods: A retrospective cohort study was performed at three transplant centers. Exposed donors were those with "recent IDU" (in the prior 12 months). Primary outcomes included (1) positive donor cultures for bacteria or Candida species, (2) recipient bacterial or Candida infection within 3 months posttransplant, and (3) recipient graft failure or death within 12 months posttransplant. Mixed effects multivariable regression models were used to evaluate the relationship between recent donor IDU and each outcome. Results: A total of 658 SOT recipients who received organs from 394 donors were included. Sixty‐six (17%) donors had a history of recent IDU. Recent IDU in donors was associated with a significantly increased odds of donor culture positivity (aOR 3.65, 95% CI 1.06–12.60, p = .04) but was not associated with SOT recipient infection (aHR 0.98, 95% CI 0.71–1.36, p = .92) or graft failure or death (aHR 0.67, 95% CI 0.29–1.51, p = .33). Conclusion: Donors with recent IDU are more likely to have positive cultures, but their recipients' outcomes are unaffected, suggesting organs from donors with recent IDU may be safely utilized. Abstract :